P53 Protein overexpression in cholangiocarcinoma arising in primary sclerosing cholangitis. Issue 2 (February 1996) - Rizzi, P M; Ryder, S D; Portmann, B; Ramage, J K; Naoumov, N V; Williams, R
Abstract : The protein encoded by the p53 tumour suppressor gene plays an important part in the regulation of cell growth. Abnormalities of this gene represent one of the most common genetic changes in the development of human cancers. This study investigated the expression of p53 protein in cholangiocarcinoma arising in association with primary sclerosing cholangitis (PSC). Of the 14 patients with cholangiocarcinoma studied, 13 had underlying PSC. The expression of p53 protein was detected immunohistochemically in paraffin wax embedded liver specimens, after microwave pretreatment. The expression of p53 protein was shown in the cholangiocarcinoma tissue of 11 of 14 (78.5%) patients. In five of 10 patients, the accumulation of p53 protein highlighted the presence of neoplastic cells in biliary tissue separate from the main tumour. These cells were mainly located in the septal bile ducts or in the accessory glands, or both, but occasionally also in large portal areas at the periphery of nerves and lymphatics, and in one case in the mucosa of an extrahepatic bile duct. No p53 protein was detectable in liver tissue obtained at the time of transplantation in 15 patients with PSC but not cholangiocarcinoma. These results show that cholangiocarcinoma development in PSC is commonly associated with abnormalities of p53 and that these occur at a late stage in the development of the malignant process. Staining for p53 protein could represent an additional criterion for the diagnosis of cholangiocarcinoma development in patients with PSC.